ARGET ATRP of styrene in EtOAc/EtOH using only Na2CO3 to promote the copper catalyst regeneration. Issue 6 (6th May 2021) - Braidi, Niccolò; Buffagni, Mirko; Ghelfi, Franco; Parenti, Francesca; Gennaro, Armando; Isse, Abdirisak A.; Bedogni, Elena; Bonifaci, Luisa; Cavalca, Gianfranco; Ferrando, Angelo; Longo, Aldo; Morandini, Ida
Abstract: "Activator regenerated by electron transfer" "atom transfer radical polymerization" (ARGET ATRP) process catalyzed by CuCl2 /tris(2-pyridylmethyl)amine (TPMA) (1/1) in ethyl acetate/ethanol (EtOAc/EtOH) for the polymerization of styrene from ethyl 2, 2-dichloropropanoate (EDCP) is described. The (re)generation of the activating Cu I complex is accomplished by Na2 CO3 without the addition of any explicit reducing agent. Differently from the analogous process operating in the presence of ascorbic acid/carbonate as the reducing system, branching is not present and control over polymerization is improved. The activation mechanism should follow a composite route, where both EtOH and TPMA contribute to the regeneration of the catalyst. The oxidation of TPMA is suggested by the absence of the ligand in the final reaction mixture and by the reduction of Cu II even in t -BuOAc/ t -BuOH, notwithstanding the very poor ability of t -BuOH as a reducing agent. Oxidative degradation of TPMA causes a progressive malfunctioning of the redox catalyst. Consequently, the polymerization rate, after a prompt start, becomes slower and slower, fixing conversions at around 50% (4.5 h). This means a gradual decrease of the free radical concentration, which develops unfavorable conditions for the reductive coupling (termination) between the bifunctional growing chains, preserving a controlled growth of the polymer. Graphical Abstract: